Upgrading patients with pacemakers to resynchronization pacing: Predictors of success - Samir Rafla; Aly Aboelhoda; Mostafa Nawar; J.Ch. Geller; Mohamed Lotfi (Alexandria Journal of Medicine, 2018)
Background: The investigations of predictors of success or failure of cardiac resynchronization therapy were studied previously. Assessment of success in patients already on dual or single pacemakers and upgraded to cardiac resynchronization therapy (CRT) were not extensively studied before. How to select patients in whom this may be the most optimal strategy is unclear. We sought to determine factors associated with success or failure in this group of patients who were already paced for heart block. Methods: 81 pts were subjected to upgrade to CRT implantation after being on pacemaker. The study was conducted in Germany. Data was presented as Median (Min.–Max.) for abnormally distributed data or Mean ± SD. for normally distributed data. Parameters that revealed no statistical significance in response: Age, sex, EF, diabetes, renal disease, GFR, MR, QRS duration (all above 150 ms), history of ablation, AF recurrence, previous pacemaker, optimization. The following parameters revealed significant influence on response to CRT: Less responders with: Higher C reactive protein (CRP), presence of tricuspid incompetence (TR), presence of pulmonary hypertension (PHN), presence of previous MI, being ischemic vs nonischemic cardiomyopathy (CM) (less responders with ischemic CM). Conclusions: The findings through light on specific parameters that predict response to upgrade to CRT after usual pacemaker. Keywords: Heart failure, Resynchronization therapy, CPR, Ischemic vs non-ischemic cardiomyopathy